2020
DOI: 10.1002/jbmr.4267
|View full text |Cite
|
Sign up to set email alerts
|

Functional Scaffold-Free Bone Equivalents Induce Osteogenic and Angiogenic Processes in a Human In Vitro Fracture Hematoma Model

Abstract: After trauma, the formed fracture hematoma within the fracture gap contains all the important components (immune/stem cells, mediators) to initiate bone regeneration immediately. Thus, it is of great importance but also the most susceptible to negative influences. To study the interaction between bone and immune cells within the fracture gap, up-to-date in vitro systems should be capable of recapitulating cellular and humoral interactions and the physicochemical microenvironment (eg, hypoxia). Here, we first d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Blood- [ 7 ] or MSC-based [ 8 ] scaffolds/hydrogels have become attractive tools for investigating physiological or delayed bone healing processes as well as developing functional bone substitutes. This is particularly important since bone substitutes often require additional biological supplementation to support bone repair.…”
Section: Introductionmentioning
confidence: 99%
“…Blood- [ 7 ] or MSC-based [ 8 ] scaffolds/hydrogels have become attractive tools for investigating physiological or delayed bone healing processes as well as developing functional bone substitutes. This is particularly important since bone substitutes often require additional biological supplementation to support bone repair.…”
Section: Introductionmentioning
confidence: 99%
“…While the gold standard of preclinical studies is animal models, these models may have limited transferability due to differences in timeline, physiologic structure, pharmacologic response, and variation in specific gene pathways across species, supporting the need for in vitro models using human cells and tissues to complement animal work ( 4 , 127 , 128 ). In vitro models have been developed over the past decade to create a more physiologically-relevant system for studying human fracture.…”
Section: Fracture Modeling Approachesmentioning
confidence: 99%
“…[169] Reports have also suggested that co-administration of deferoxamine with other angiogenic signaling cues promotes hypoxic stimulation of the vascular intermediaries as compared to the control group. [170,171] Collagen type 1 is the major protein-polymer found in ECM, contributing to the strength and stiffness which is laid down by the osteoblasts and fibroblasts. Its properties can be modified to fabricate bone scaffolds and vascularized grafts to aid neovascularization.…”
Section: Addition Of Biological Biochemical or Natural Compounds To E...mentioning
confidence: 99%
“…Simvastatin doping onto mesoporous HA microsphere‐collagen composite causes VEGF, HIF‐1α expression from stem cells with the interdependent intensification of tubule formation, cell migration illustrating pro‐angiogenesis [169] . Reports have also suggested that co‐administration of deferoxamine with other angiogenic signaling cues promotes hypoxic stimulation of the vascular intermediaries as compared to the control group [170,171] …”
Section: Introductionmentioning
confidence: 99%